2017
DOI: 10.4236/health.2017.94046
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Self-Efficacy for Exercise at 12 Weeks after Exercise Education in Diabetic Patients

Abstract: The purpose of this study was to investigate whether self-efficacy for exercise decreased 12 weeks after educational intervention in diabetic patients and whether this had an effect on glycemic control. Thirty-eight diabetic patients underwent a 2-week educational program and were then followed for 12 weeks after discharge. The intervention program was delivered by several types of medical professionals. Lectures on exercise were given by a physical therapist, who tailored exercise instructions for individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, few previous studies have examined the long-term changes over six months or longer. In fact, in our report on the effects of SE with respect to exercise and glycemic control at 12 weeks after guidance, there was no noted correlation between SE with respect to exercise and glycemic control at 12 weeks after the instruction, and the need for the long-term study was reported 10 ) . If a correlation between SE and stage of change can easily evaluate the psychological state of exercise and long-term glycemic control is recognized, it may be possible to predict the patient course based on a psychological evaluation.…”
Section: Introductionmentioning
confidence: 64%
“…However, few previous studies have examined the long-term changes over six months or longer. In fact, in our report on the effects of SE with respect to exercise and glycemic control at 12 weeks after guidance, there was no noted correlation between SE with respect to exercise and glycemic control at 12 weeks after the instruction, and the need for the long-term study was reported 10 ) . If a correlation between SE and stage of change can easily evaluate the psychological state of exercise and long-term glycemic control is recognized, it may be possible to predict the patient course based on a psychological evaluation.…”
Section: Introductionmentioning
confidence: 64%